Human Library and its application: an educational innovation approach at the Faculty of Arts, University of Colombo - Manatunga, P.K.S.; Silva, M.A.L.; Adhikari, H.I.S.M. (The Library, University of Colombo., 2020)
The Human Library concept was introduced to the Sri Lankan university sector by the Main Library, University of Colombo in 2016. Since then, the Human Library has been a calendar event of the Library Network of the University of Colombo. The literature on how the students and experts were influenced by the Human Library projects is available in the global context, but it is very rare in the Sri Lankan context. The present study attempts to fulfil the existing gap and thus the research will add new knowledge to the respective knowledgebase. The overall objective of this study is to evaluate the possibility of using the Human Library as a new approach for learning. The study was conducted during the3rdHuman Library programme conducted as part of the orientation programme for the undergraduates of the Faculty of Arts in 2019.A mixed-method approach was adopted in the present study. A self-designed, structured questionnaire was the main research tool for data collection followed by interviews with selected participants. The total population was 800 students, and based on Krejcie and Morgan’s (1970) table, a sample of 260 was selected. Thirty-five human experts were purposively selected for the event from different Social Science disciplines. Both human experts and the students had favorable attitudes towards the Human Library approach, which they considered to be well-suited to gain a broad spectrum of knowledge on Humanities and Social Sciences. Although 97.3% of the students expressed that, this was the first experience as a reader in a Human Library, 76.9% were highly satisfied with the concept and 74.2 % were highly satisfied with the selection of experts. Eighty percent accepted Human Library as a new initiative to get familiarize with the learning environment and as an innovative learning approach. With respect to the experts, for 50% of the respondents this was the first experience as a Human Book. All were highly satisfied with the concept. The experts identified the benefits of being living books that can positively influence the students. All the Human experts agreed that the concept of Human Library can be applied as a novel innovation for education, and they agreed to continue it as a calendar event. The present study suggests that the Human Library is beneficial for interactions between the subject specialists and the students reducing the gap and should be deployed as a new learning approach in the Faculty of Arts.
Keywords: Human Library, Learning approach, University of Colombo